Malignant Hypertension: Damaging Disease of the Eye and Beyond - Carr, Emily Rose (Canadian Journal of Optometry, 2020)
Abstract: Case review follows a 49-year-old patient with malignant hypertension with retinopathy and resultant visual decline. Case Report: Severely uncontrolled hypertension manifested as malignant hypertensive retinopathy. The patient presented with substantial retinal and visual changes and was monitored over 6 months. While the patient experienced marked improvement in visual acuity, significant retinal damage occurred and the patient experienced persistent qualitative vision and visual field loss. Discussion: Observed fundus changes are consistent with advanced risk for morbidity and mortality associated with hypertension. Management of systemic disease is a critical step in reversing retinal manifestations and minimizing the risk for permanent vision loss. The criticality of systemic treatment also applies to lowed risk for systemic vascular events that may compromise quality of life. This case demonstrates that improvement in Snellen acuity does not always parallel functional visual improvement. Eye care providers managing these cases should consider both systemic risks and visual outcome.